Introduction of potato (Solanum tuberosum) in hot arid region of north-western Rajasthan (Current Horticulture, 2024)
The experiment was conducted at ICAR-CIAH, Bikaner, (Rajasthan) to assess the performance of potato (Solanum tuberosum) cultivars in hot arid region during 2015-16 and 2016-17. Potato cultivars Kufri Khyati, Kufri Garima, Kufri Chipsona4, Kufri Pukhraj, Kufri Frysona, Kufri Surya and Kufri Jyoti, were grown under sprinkler and drip irrigation system with recommended management practices. Under sprinkler irrigation, Kufri Chipsona 4 gave highest yield (534.8 q/ha), followed by Kufri Frysona (479.7 q/ha) and Kufri Jyoti (465.1 q/ha), Kufri Garima (430.9 q/ha), Kufri Surya (398.6 q/ha) and Kufri Khyati (387.6 q/ha), while minimum yield was observed in Kufri Pukhraj (338.9 q/ha). In drip irrigation, Kufri Frysona gave highest yield (435.37 q/ha), followed by Kufri Chipsona4 (428.67 q/ha), Kufri Garima (374.45 q/ha) and Kufri Jyoti (344.58 q/ha) Kufri Pukhraj (203.99 q/ ha). The tuber yield of all varieties was also classified into large (>75 g), medium (25-75 g) and small (71.40% tubers were under large-sized category. Similarly, dry matter content was highest (22.22%) in Kufri Frysona and minimum in Kufri Khayati (15.09%) at 90 days of harvesting. The appearance of the tuber though varies with variety but it was very shining golden yellowish and was better than its recommended areas of Indo-gangetic plains. Based on tuber yield, size of tubers, dry matter content and appearance of tubers; it is recommended that Kufri Chipsona 4 and Kufri Frysona are suitable for processing types, while Kufri Garima and Kufri Jyoti as table types for cultivation under sprinkler system in hot arid region of Rajasthan.
Keywords: Agronomic-use efficiency (AUE); Net returns; Tuber yield; Hot arid region